Investigation of Compresibility and Strength Behaviour of Deposited Dredged Slurries by Laboratory and Field Tests - Bicer, Perihan; Kilic, Havvanur; Ozener, Pelin (TURKISH CHAMBER CIVIL ENGINEERS, 2021)
In this study, the consolidation and the strength behavior of Halic dredged slurry stored at a disposal site were investigated through laboratory and field tests. For this purpose, four large scale model tests and a sedimentation test were carried out in the laboratory in order to simulate the consolidation process of the dredged material under self weight conditions. In these tests in order to investigate the compressibility behaviour, consolidation tests were carried out on the undisturbed samples recovered from the sedimentation tests. Additionally, vane test were performed in the large scale model tests to determine the undrained shear strength variation with depth. The coefficient of consolidation (cv) values obtained from the settlements measured in model tests and undrained shear strength values measured from vane tests were determined to be 0.91 - 10.72 m(2)/year and 4-20 kPa, respectively. The undrained shear strength values determined from the field tests carried out at the site 13 years after the storage of dredged slurry were determined to be 4-20 kPa based on SPT-N tests and UU tests. As a result of the field tests performed at the disposal site, it is determined that 25m thick dredged material deposited at the site has low bearing capacity and high compressibility characterisctics.Y
Keywords: Self weight consolidation; surcharge loads; dredged sludge; shear strength; compressibility; SELF-WEIGHT CONSOLIDATION; NON-LINEAR CONSOLIDATION; SEDIMENTATION BEHAVIOR; SATURATED CLAYS; MODEL; Engineering